Pemanfaatan Sampah Plastik sebagai Bahan Daur Ulang melalui Metode Ecobrick - Raihan, Muhammad; Pradana, Muhammad Yudha; Hakim, Arief Rahman; Fadhil Hasan R, Hans Mokhammad; Chaerani, Ika Tania; Safitri, Saktya Dea; Nurrohmah, Siti; Putri, Hasna Tantowi; Afitri, Windy Dwi; Ananda , Dhimas Aryo Vipha (Universitas Muhammadiyah Yogyakarta, 2025)
The problem of plastic waste in Druju Hamlet, Ngawen District, Klaten Regency, is caused by low public awareness and lack of waste management facilities. This program aims to increase public awareness and skills in plastic waste management through the ecobrick method, which is the compaction of plastic into bottles as an environmentally friendly construction material. Activities include socialization, waste collection and cleaning, making ecobricks, and implementation in the form of an installation of the inscription